Responding to the Opioid Epidemic: Educational Competencies for Pain and Substance Use Disorder from the Medical Schools of the University of California. Issue 1 (14th December 2020) - Servis, Mark; Fishman, Scott M; Wallace, Mark S; Henry, Stephen G; Ziedonis, Doug; Ciccarone, Daniel; Knight, Kelly R; Shoptaw, Steven; Dowling, Patrick; Suchard, Jeffrey R; Shah, Shalini; Singh, Naileshni; et al.
Abstract: Objective: The University of California (UC) leadership sought to develop a robust educational response to the epidemic of opioid-related deaths. Because the contributors to this current crisis are multifactorial, a comprehensive response requires educating future physicians about safe and effective management of pain, safer opioid prescribing, and identification and treatment of substance use disorder (SUD). Methods: The six UC medical schools appointed an opioid crisis workgroup to develop educational strategies and a coordinated response to the opioid epidemic. The workgroup had diverse specialty and disciplinary representation. This workgroup focused on developing a foundational set of educational competencies for adoption across all UC medical schools that address pain, SUD, and public health concerns related to the opioid crisis. Results: The UC pain and SUD competencies were either newly created or adapted from existing competencies that addressed pain, SUD, and opioid and other prescription drug misuse. The final competencies covered three domains: pain, SUD, and public health issues related to the opioid crisis. Conclusions: The authors present a novel set of educational competencies as a response to the opioid crisis. These competencies emphasize the subject areas that are fundamental to the opioid crisis: pain management, the safe use of opioids, and understanding and treating SUD.